Registros dos processos participativos sob a ótica do mapeamento: o caso do zoneamento ecológico-econômico no Vale do Ribeira - Parada, Isadora Le Senechal (2018)
The Ecological-Economic Zoning (EEZ) formulation must, necessarily, be a participatory process, comprising the methodological adaptations according to the regional peculiarities. This research aimed to study, from the perspective of the participatory mapping, in three failed attempts of the Vale do Ribeira EEZ to formalize this legal instrument (1st period: from 1980 to 1998; 2nd period: from 1999 to 2005; 3rd period: from 2010 to 2014). The methodology was based on case study and content analysis, from four data sources: Geographic Database (GDB), Minutes of Meetings, Processed Documents and Interviews. Only documents and interventions directly related to the map were analyzed, discarding the conceptual and theoretical character ones. In the three periods, it was noted the existence of social participation strategies. In the first two periods, there was a predominance of participatory mapping based on cartographic (on paper), while in the third period, there was also participatory mapping with GIS Desktop. The minutes of 122 meetings and registrations of 191 geographical interventions were analyzed, most of them from the third period. A low processing of documents was observed, with a majority (65%) sent by the coordinating body of the EEZ. Regarding the records in the BDG, of the 1,495 existing polygons, 65.2% presented some description or justification of the framework. The approach of key actors with geotechnical tools is also important to evaluate the process as a whole, and not just the results. The evaluation showed that all forms of registration (meeting minutes, GDB and documentation) complement each other in the understanding of the process dynamics. Minutes of meetings are fundamental to record the conceptual discussions and details of the arguments that led to the decision making by the group, but they also make it difficult to retrieve the discussions in future meetings and to do the direct correlation with the map. On the other hand, the direct insertion in the attribute table during the discussion, proves to be effective both for the agility of the registry and for the subsequent rescue of the discussion. This study sought to demonstrate that there has been progress in the development of participatory techniques, but also to highlight the needs to improve the debate about these works’ methodologies and criteria. The approach of the stakeholders with geotechnology is also be seen as a positive result, since it brings empowerment and greater knowledge about the work. The use of GDB as a complementary method for the registration of participatory processes deserves to be improved, with the development of new techniques that allow the storage of the history of modifications made on the map.